2019
DOI: 10.1021/acsbiomaterials.9b01281
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nano and Collagen-Based Therapeutic Materials for Skin Repair

Abstract: A novel strategy is needed for treating nonhealing wounds, which is able to simultaneously eradicate pathogenic bacteria and promote tissue regeneration. This would improve patient outcome and reduce the number of lower limb amputations. In this work, we present a multifunctional therapeutic approach able to control bacterial infections, provide a protective barrier to a full-thickness wound, and improve wound healing in a clinically relevant animal model. Our approach uses a nanoengineered antimicrobial nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…A representative example of this was recently reported by part of our team when assessing bacterial biofilm prevention (P. aeruginosa) in skin repair. In that study, diabetic mice showed impaired wound healing and were more prone to bacterial infection, when compared with their nondiabetic pairs (Lazurko et al, 2020). Another important factor to consider as a drawback for in vivo models of biofilms rely on the variability of methodologies for evaluating and quantifying biofilm formation (Table 3).…”
Section: Recently Developed In Vivo Biofilm Modelsmentioning
confidence: 98%
“…A representative example of this was recently reported by part of our team when assessing bacterial biofilm prevention (P. aeruginosa) in skin repair. In that study, diabetic mice showed impaired wound healing and were more prone to bacterial infection, when compared with their nondiabetic pairs (Lazurko et al, 2020). Another important factor to consider as a drawback for in vivo models of biofilms rely on the variability of methodologies for evaluating and quantifying biofilm formation (Table 3).…”
Section: Recently Developed In Vivo Biofilm Modelsmentioning
confidence: 98%
“…Previous reports agree that the complex cellular interactions and molecular pathways involved in wound healing can be enhanced by mimicking the physicochemical properties of different skin layers. Hence, multifunctional biomaterials have moved into the focus of skin tissue engineering to support the versatile requirements of wound healing by providing tailored topography, molecular composition, and good permeability to promote nutrient supply as well as protection against microbes. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could be seen that Si1.0 was able to enhance cellular proliferation, which was in accordance with the proliferation results discussed above. In addition, MMP9 belongs to a family of proteinases known as matrix metalloproteinases, which are commonly known to be involved in degrading the extracellular matrix and are involved in regulating cell development, especially in cancer evolution and wound regeneration [ 49 ]. Matrix metalloproteinases (MMPs) have been reported to be present in both acute and chronic wounds and are critical in regulating the extracellular matrix degradation and deposition that are crucial for wound re-epithelization.…”
Section: Resultsmentioning
confidence: 99%